Design of portable coconut milk extractor - Kenneth Hamilton, Anak Munsang (Universiti Malaysia Sarawak (UNIMAS), 2008)
Coconut milk extractor is a device to extract fresh coconut milk. It becomes an alternative for conventional extracting method nowadays. This type of method is more reliable in term of processing time, hygiene, safety and requires less processing method. This thesis presents the process of design, fabrication, and experiment analysis of a portable mock up model coconut milk extractor. The target group and potential customers are busy urban society especially working housewives and Small and Medium Industries (SMI). The aim of the project is to reduce size and cost of the machine than the one which is used in this industry. Thorough extracting methods and market studies are discussed in order to improve the design. Material availability and fabrication utilities are considered in the machine prototype construction. Final testing and performance of the prototype such as the amount of coconut milk can be extracted and the efficiency of the prototype is measured. The design is hoped to be able to extract a sufficient amount of coconut milk and acts as a user friendly gadget in the kitchen hence compete against other existing machines available in the market today.